Obstacles in Proving the Crime of Money Laundering by Law Enforcement in Indonesia - Sulistyo, Edhei; Pujiyono, Pujiyono; Cahyaningtyas, Irma (Jurnal Ius Constituendum, 2024)
This research aims to determine the obstacles to proving criminal acts of money laundering by law enforcement in Indonesia. The legal view regarding the crime of money laundering in Indonesia is that as long as there is no guilty verdict against the perpetrator of the predicate crime, then anything related to assets cannot be carried out. In practice, law enforcement still uses follow-up measures for money laundering suspects who prioritize punishment over asset recovery. This research focuses on proving the obstacles to the implementation of the Money Laundering Crime Law in the Police, Prosecutor's Office, and Corruption Eradication Commission. The research method in this writing uses doctrinal methods (juridical-normative) and non-doctrinal methods (juridical-empirical or socio-legal). The research results show that there still needs to be more conflict between the interests of law enforcement and the police, especially in terms of proving and recovering state losses. Obstacles to asset recovery that prosecutors can carry out are obstacles for prosecutors who are not given the authority to investigate criminal acts of money laundering that occurred before the 2010 Law on Money Laundering because the old law did not regulate the prosecutors' authority regarding this matter. Affairs. Criminal investigation. Money laundering. Likewise with the Corruption Eradication Commission, regarding the provisions of Article 69 concerning predicate crimes, they do not have to be proven first. Obstacles to Proving the Crime of Money Laundering by Law Enforcement in Indonesia.